Penanganan limbah krom dengan metode destruksi kimia - Suliestiyah Wiryodiningrat; Endro Kismolo; Prayitno Prayitno (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2007)
The treatment of chrome waste water was conducted by chemical destruction method. Chromium recovery process that at the same time lowering the chrome content is considered the best solution so far. The treatment of chrome The treatment of chrome waste water was done by chemical process using Magnesium Oxide and Lime to produce Sludge of Chromium performed. By the process of chemical destruction method using Sulphuric Acid, Chrome Sulphate or Chromosal powder that can be used as an alternative tanning agent can be obtained. It can be concluded from the research that destruction process of Chrome Hydroxide Sludge of Lime Process requires speed of stirring 100 rpm. At this state, the content of soluble Solid Substance in Chromium Sulphate Liquor was 5.125 g/l, and the solubility of chromosal in water was 99.15%, whereas for Sludge of Chrome Hydoxide from Magnesium Oxide process, the best speed of stirring was 150 rpm, with soluble solid substance in the Chrome Sulphate was 4.085 g/l and solubility of Chromosal powder in water was 99.54%. Key word : Chrom, chemical destruction, waste water. ABSTRAKTelah dilakukan penanganan limbah krom dengan metode distruksi kimia. Proses mendapatkan kembali kromium dan sekaligus menurunkan kadar krom limbah industri penyamakan kulit adalah merupakan pemecahan masalha yang terbaik. Penanganan limbah krom dilakukan dengan proses kimiawi menggunakan magnesium oksida dan kapur untuk membentuk lumpur krom. Melalui proses distruksi kimia dengan asam sulfat, dapat diperoleh krom sulfat atau serbuk kromosal yang dapat digunakan sebagai bahan penyamak kulit alternatif. Dari percobaan dapat disimpulkan bahwa pada proses distruksi lumpur krom hidroksida dari proses kapur membutuhkan kecepatan pengadukan sebesar 100 rpm. Pada kondisi ini kadar zat padat terlarut dalam larutan krom sulfat sebesar 5,125 g/l, dan nilai kelarutan dalam air pada produk serbuk kromosal sebesar 99,15%. Sedangkan untuk lumpur krom hidroksida hasil pengendapan menggunakan MgO kecepatan pengadukan terbaik dicapai pada 150 rpm, dengan nilai kadar zat padat terlarut dalam produk larutan krom sulfat sebesar 4,085 g/l dan nilai kelarutan dalam air pada produk serbuk kromosal sebesar 99,54^. Kata Kunci : Krom, destruksi kimia, limbah cair.